Relevance of Microvascular Flow Assessments in Critically Ill Neonates and Children: A Systematic Review. Issue 4 (April 2020) - Maitoza, Laura A.; Neeman, Eitan; Funaro, Melissa; Pierce, Richard W.
Abstract : Objectives: Resolution of impaired microvascular flow may lag the normalization of macrocirculatory variables. The significance of microcirculatory dysfunction in critically ill children and neonates is unknown, but microcirculatory variables can be measured using Doppler or videomicroscopy imaging techniques. We outline the current understanding of the role of the microcirculation in critical illness, review methods for its assessment, and perform a systematic review of how it has been monitored in critically ill neonates and children. Design: Systematic review (PROSPERO CRD42019117993). Setting: Not applicable. Subjects: Not applicable. Interventions: None. Measurements and Results: We systematically searched MEDLINE, EMBASE, PubMed, and Web of Science. We included studies of critically ill patients 0 to 18 years old investigating microcirculatory blood flow. Two reviewers analyzed abstracts and articles. Results were qualitatively analyzed due to study heterogeneity. A total of 2, 559 abstracts met search criteria, of which 94 underwent full-text review. Of those, 36 met inclusion criteria. Seven studies investigated microcirculatory changes in critically ill children. Twenty studies investigated the microcirculatory changes in neonates with variable diagnoses compared with a diverse set of clinical endpoints. Nine studies assessed the effects of age, sex, and birth weight on microvascular flow in neonates. Across all studies, microcirculatory dysfunction was associated with poor outcomes and may not correlate with observed macrovascular function. Conclusions: Assessment of microvascular flow in critically ill children and neonates is possible, although significant challenges remain. In many such patients, microvascular blood flow is disrupted despite medical management targeting normalized macrovascular variables. Future studies are needed to define normal pediatric microvascular flow variables and to assess the impact of patient and treatment factors on its function. Abstract : Supplemental Digital Content is available in the text.